Base-promoted synthesis of 1H, 3H-pyrrolo[1, 2-c]thiazol-3-imine derivatives via [3+2] annulation of 2-alkynylpyrroles with isothiocyanates. Issue 47 (24th November 2016) - Zhang, Ziyin; Guo, Biao; Zhou, Yiming; Hua, Ruimao
Abstract: Base-promoted [3+2] annulation of 2-alkynyl pyrrole with isothiocyanate affording 1 H, 3 H -pyrrolo[1, 2- c ]thiazol-3-imine derivatives has been developed. The control experiments suggest that the reaction proceeds via simple nucleophilic attack followed by intramolecular addition. The present cascade reaction provides a facile one-pot synthesis of 1 H, 3 H -pyrrolo[1, 2- c ]thiazol-3-imine derivatives under mild conditions with good yields and high regioselectivity. Graphical abstract: